Multi-dimensional perspective of homestay sustainability in Malaysia moderated by carrying capacity - Balasingam, Ann Selvaranee (2018)
The sustainability of the Malaysian homestay program that has been in existence for the last 30 years is questionable due to several issues surrounding the program. Firstly, are the economic issues of competition from the rising number of unregistered homestay operators, employment, and the multiplier effect. Secondly, are the institutional issues of the lack of governance at the federal, state and village level of administration. Thirdly, is the lack of environmental concerns within the homestay program and fourthly, are the sociocultural issues related to the lack of youth involvement, the extent of sociocultural understanding and tourist safety and security. The objective of this study is to investigate homestay sustainability from four stakeholders’ perspectives; homestay owners, relevant government officials, local residents, and tourists from four dimensions; economic, institutional, environmental and sociocultural (EIES) moderated by carrying capacity. The theory underpinning this study is the Theory of Development and the Stakeholder Theory. This study employed the quantitative research method using a five-point Likert scale. The sampling strategy is random probability cluster sampling for the homestay owners and non-probability sampling for the government officials, local residents and tourists. A total of 254 homestay owners, 115 government officials, 57 local residents, and finally 96 tourists responded to the survey questionnaires. This study was done across multiple states in West Malaysia. IBM SPSS Statistics and Partial Least Square (PLS) approach to Structural Equation Modeling (SEM) were utilized to analyze the data and justify the three main hypotheses. There are three main hypotheses and four specific hypotheses for this study. The first main hypothesis states that there is a significant relationship between each EIES dimension and homestay sustainability. From the first main hypothesis, there are four specific hypotheses. The first specific hypothesis is that there exist a significant relationship between the economic dimension and homestay sustainability. The second specific hypothesis is that there exist a significant relationship between the institutional dimension and homestay sustainability. The third and fourth specific hypothesis are that there exist a significant relationship between the environmental dimension and homestay sustainability and that there exist a significant relationship between the sociocultural dimension and homestay sustainability. The second main hypothesis is that the carrying capacity moderates the relationship between the economic, institutional, environmental and socio-cultural dimensions and homestay sustainability. The third main hypothesis states that there is a significant relationship between homestay owners’ years of involvement and homestay sustainability. This study confirms the significant relationship for the first, second and third hypothesis.The findings of this study provide theoretical and practical contributions. The main theoretical contributions are the use and validation of the institutional dimension through a local level homestay sustainability framework. Secondly, four uniquely identified indicators; destination competitiveness, biophysical characteristics, social factors and management policies with limited past empirical evidence were tested and resulted in statistical significance. Finally, the use of SEM PLS provides added empirical analysis for research related to sustainable tourism. The practical contribution is primarily for the homestay owner to be more focused on promoting the uniqueness of the Malaysian homestays. The policy implications for the government at the federal level is to regulate the Malaysian homestay program formally. Lastly, the area that lacks awareness and concern is the environmental dimension. In conclusion, this study has directly contributed to the program development and suggest policy and procedural improvements towards the sustainability of the Malaysian homestay program.